Implementation of behavioristic theory in online learning of Indonesian lessons in class IV of elementary school - Nurani, Maya (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to determine changes in behavior (behavioristic) in Indonesian language learning in reading, writing, and listening skills in grade IV at SDN Karang Entang Bangkalan. This research uses qualitative research methods conducted online. The type of data in this research is quantitative and descriptive qualitative obtained from the sample group data, then divided by the number of these samples. Based on the results of the research conducted, the percentage results of listening skills were 72% in very good criteria. In the reading skills material, it is 95% in very good criteria. In the material of writing skills, it is 81% in very good criteria. From these results, it is stated that learning Indonesian on the material of listening, reading and writing skills using behavioristic theory, the teacher is able to change and shape student behavior, including increasing and increasing knowledge, increasing attitudes, and increasing skills and making learning more effective and meaningful.